2017
DOI: 10.1039/c7ee01738c
|View full text |Cite
|
Sign up to set email alerts
|

Balancing electron transfer rate and driving force for efficient photocatalytic hydrogen production in CdSe/CdS nanorod–[NiFe] hydrogenase assemblies

Abstract: We describe a hybrid photocatalytic system for hydrogen production consisting of nanocrystalline CdSe/CdS dot-in-rod (DIR) structures coupled to [NiFe] soluble hydrogenase I (SHI) from Pyrococcus furiosus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
110
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(114 citation statements)
references
References 56 publications
4
110
0
Order By: Relevance
“…One approach to motivate and inspire progress has been to use enzymes as the catalysts in model solar conversion devices and photocatalytic complexes. [1][2][3][4][5][6][7][8][9][10][11][12] Enzymes are valuable because evolution has taken them close to perfection -their suitability being gauged in terms of their high substrate specificities, high turnover rates, low overpotential requirements and use of abundant elements (e.g. Fe, Mn, Ni and Cu) instead of precious metals.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One approach to motivate and inspire progress has been to use enzymes as the catalysts in model solar conversion devices and photocatalytic complexes. [1][2][3][4][5][6][7][8][9][10][11][12] Enzymes are valuable because evolution has taken them close to perfection -their suitability being gauged in terms of their high substrate specificities, high turnover rates, low overpotential requirements and use of abundant elements (e.g. Fe, Mn, Ni and Cu) instead of precious metals.…”
mentioning
confidence: 99%
“…For example, using molecular biology procedures, it is possible to design and produce an enzyme for specific attachment of a suitable photosensitizer in such a position that allows rapid and direct electron injection into the enzyme's internal relay system. Examples of where enzymes have been used in model systems include their direct immobilization on semiconductors such as TiO 2 , 11 CdX (X = S, Se, Te), 1,8,9 and In 2 S 3 , 17 electrodes (bulk or nanostructured carbon, [18][19][20] TiO 2 , 21,22 Au 23 ) and molecular complexes with photoactive or conductive materials. 1,[7][8][9][10]12,[24][25][26] In solar fuels research it is always necessary to close the cycle efficiently using an external electron donor: the latter is ideally water, but this requires a second special catalyst and knowledge has progressed mainly by focusing on one side of the cycle and using a 'blunt tool' in the form of an innocuous, non-selective agent such as an amine, present in high concentration.…”
mentioning
confidence: 99%
“…Chica et al. reported a hybrid photocatalytic system for H 2 production containing nanocrystalline CdSe/CdS dot‐in‐rod (DIR) components coupled to Pf [NiFe] H 2 ase . Electrons were shuttled to the catalyst by a redox mediator: methyl viologen (MV 2+ , E m =−446 mV) or propyl‐bridged 2–2′‐bipyridinium (PDQ 2+ , E m =−550 mV).…”
Section: Electrochemical and Biochemical Applicationmentioning
confidence: 99%
“…5 In another study reported by Changwen Hu et al, Cd 0.5 Zn 0.5 SQDs@C 3 N 4 photocatalyst has been stated to show remarkable hydrogen production performance and high stability under visible light, which were attributed to strong electronic coupling between Cd 0.5 Zn 0.5 S and g-C 3 N 4. 13 Different methods such as thermal annealing, 14 precipitation, 15 and high pressure application 16 have been used to control the crystal structure and obtain hexagonal crystal structure. However, the PC activity, photo-stability, and efficiency of this photocatalyst still need to be improved.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the crystal structure of composite remarkably affects the PC activities of semiconductors. 13 Different methods such as thermal annealing, 14 precipitation, 15 and high pressure application 16 have been used to control the crystal structure and obtain hexagonal crystal structure. Photocatalysts with a cubic crystal structure may have the limits such as low thermal stability, poor visible light adsorption, and low hydrogen production rate.…”
Section: Introductionmentioning
confidence: 99%